A Pilot Study Examining the Relationship among Crohn Disease Activity, Glucagon-Like Peptide-2 Signalling and Intestinal Function in Pediatric Patients. (2013) - Sigalet, David L; Kravarusic, Dragan; Butzner, Decker; Hartmann, Bolette; Holst, Jens J; Meddings, Jon
Abstract : BACKGROUND/OBJECTIVES: The relationship between the enteroendocrine hormone glucagon-like peptide 2 (GLP-2) and intestinal inflammation is unclear. GLP-2 promotes mucosal growth, decreases permeability and reduces inflammation in the intestine; physiological stimulation of GLP-2 release is triggered by nutrient contact. The authors hypothesized that ileal Crohn disease (CD) affects GLP-2 release. METHODS: With ethics board approval, pediatric patients hospitalized with CD were studied; controls were recruited from local schools. Inclusion criteria were endoscopy-confirmed CD (primarily of the small intestine) with a disease activity index >150. Fasting and post-prandial GLP-2 levels and quantitative urinary recovery of orally administered 3-O-methyl-glucose (active transport) and lactulose/mannitol (passive) were quantified during the acute and remission phases. RESULTS: Seven patients (mean [± SD] age 15.3±1.3 years) and 10 controls (10.3±1.6 years) were studied. In patients with active disease, fasting levels of GLP-2 remained stable but postprandial levels were reduced. Patients with active disease exhibited reduced glucose absorption and increased lactulose/mannitol recovery; all normalized with disease remission. The change in the lactulose/mannitol ratio was due to both reduced lactulose and increased mannitol absorption. CONCLUSIONS: These findings suggest that pediatric patients with acute ileal CD have decreased postprandial GLP-2 release, reduced glucose absorption and increased intestinal permeability. Healing of CD resulted in normalization of postprandial GLP-2 release and mucosal functioning (nutrient absorption and permeability), the latter due to an increase in mucosal surface area. These findings have implications for the use of GLP-2 and feeding strategies as a therapy in CD patients; further studies of the effects of inflammation and the GLP-2 axis are recommended.